English Major Students’ Perceptions of Ethical Use of ChatGPT in Academic Learning - Anggita, Mohammad Anjas; Sakhiyya, Zulfa (Journal of English Language and Education, 2026)
The integration of artificial intelligence tools such as ChatGPT has increasingly influenced academic learning in higher education. While previous studies highlight ChatGPT's usefulness in supporting students’ academic tasks, limited research has examined students’ ethical awareness when using AI tools in academic contexts. This study aims to investigate English major students’ perceptions of the ethical use of ChatGPT in academic learning. A descriptive quantitative design was employed using a questionnaire distributed to 23 English major students. The data were analyzed using percentages and mean scores to examine students’ perceptions of ChatGPT’s usefulness, ease of use, and ethical considerations. The findings indicate that students generally perceive ChatGPT as a helpful learning tool that supports idea, comprehension of academic materials, and task completion. However, students also demonstrate awareness of the importance of verifying AI-generated information and maintaining originality. The study concludes that ChatGPT can support academic learning when used responsibly and ethically.